1968
DOI: 10.1021/ac60264a047
|View full text |Cite
|
Sign up to set email alerts
|

Atomic absorption analysis of ferrites

Abstract: Two important conclusions can be drawn from this study: that potassium iodate is stable in the melt at this temperature for periods of at least hours, and that a method has been developed which can be used to determine iodate (and other stable positive oxidation states of iodine) sampled from tMs fused salt medium. and would, therefore, introduce positive errors in the analyses. Table I presents the data obtained for the determination of potassium iodate in the eutectic melt by this method. With reference to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1972
1972
1985
1985

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…25 (44) While (diethylamino)sulfur trifluoride has been purified via distillation on several occasions without incident, explosions have been reported with this reagent during this process. 46 We have since found that the crude reagent works equally as well as the distilled compound in this reaction. (45) Cochran, J. Chem.…”
Section: Methodsmentioning
confidence: 92%
See 1 more Smart Citation
“…25 (44) While (diethylamino)sulfur trifluoride has been purified via distillation on several occasions without incident, explosions have been reported with this reagent during this process. 46 We have since found that the crude reagent works equally as well as the distilled compound in this reaction. (45) Cochran, J. Chem.…”
Section: Methodsmentioning
confidence: 92%
“…Cholesterol levels were determined by using the Liebermann-Burchard method on a Technicon autoanalyzer. 46 Lipoprotein levels were determined by densiometric analysis of lipoprotein fractions separated by disc gel electrophoresis using a Quick-Disc Lipoprotein Gel Tube Kit (Ames Co.) and a Clifford Model 750 Densitometer (Medfield, Mass. ).37 The values listed in Table III were analyzed by using a Student's t test and are accompanied by the standard error of the mean (SEM).…”
Section: Methodsmentioning
confidence: 99%